THE TECHNOLOGICAL SCHEME OF PRODUCE MEAT SEMI FINISHED PRODUCTS UNDER MARINADE BASED ON FETUS SORBUS AUCUPARIA - M. S. Volkhonskaya; G. G. Pervyshina; T. L. Kamoza (Современная наука и инновации, 2022)
It was developed the technological scheme of production of emulsion-based marinades with the addition of fruits ofSorbus Aucu-paria. The justification of selection of plant materials and gathering in the territory of Krasnoyarsk region is given